TANGGAP BEBERAPA VARIETAS JAGUNG (Zea mays L.) TERHADAP PEMBERIAN PUPUK ORGANIK - Jenni Maria Hutapea Jenni Maria Hutapea Jenni Maria Hutapea; Mbue Kata Bangun Mbue Kata Bangun Mbue Kata Bangun; Emmy Harso Kardhinata (Universitas Sumatera Utara, 2013)
Maize is a staple food of rice substitution with a good fibre so that maize requirement alwaysmount every year. But, soil fertility supporting growth and produce the maize downprogressively with the inorganic fertilizer use. For that, required correct variety maize owninggood respon with the organic fertilizer gift. The objective of this research aim to know theresponse on growth and yield some maize varieties to organik fertilizer was done in UPTBalai Benih Induk Tanjung Selamet, Deli Serdang, Medan from April until July 2012. Thisresearch using by Randomized Block Design with two factors. The first factor are threevarieties of maize: V1:Bisma, V2:Pioneer 12, V3:SHS 4. The second factor is organicfertilizer by five levels: G0:(0g/plant),G1:75g/plant,G2:150g/plant,G3:NPK 8,4g andG4:75g/plant+ NPK. Data were analyzed with Analysis of Variance (ANOVA) andcontinued with Tukey test.The result showed that varieties were significantly different to parameters plantheight, wide of leaf, stem of corn and seed of corn. Organic fertilizer was significant differentto plant height, and wide of leaf. The interaction of varieties and organik fertilizer weresignificant effect to seed of corn production.